Principles of Curriculum Development in an Effort to Improve Learning Quality - Ferawati Butolo; Lutfia; Nur Ilmi Harun; Nurmiati Mooduto; Sri Intan Ismail; Sintiani Akuje; Rasmin Walenta; Rahmawati Malik; Febriyanti Ibrahim; MarsellaD.Gui (MultiTech Publisher, 2023)
One important component of the education system is the curriculum. The curriculum holds a key position in education, because it is related to the direction, content and process of education which eventually establishes the nature and credentials of an educational program's alumni institution. In this study the authors used library research methods. Curriculum development uses principles that have developed in everyday life or creates new principles. Therefore, in the implementation of the It is possible to utilize principles in curriculum in educational institutions that differ from those used in other educational institutions. so there will be many principles used in curriculum development